The Ongoing Impact of COVID-19 on Pediatric Obesity - Domenico Iacopetta; Alessia Catalano; Jessica Ceramella; Michele Pellegrino; Maria Marra; Elisabetta Scali; Maria Stefania Sinicropi; Stefano Aquaro (MDPI AG, 2024)
In the developed world, pediatric obesity (PO) has been a major health concern since the last century, and this condition may lead to detrimental life-long physical and mental comorbidities. Currently, its prevalence has increased in low- and middle-income countries and in many high-income countries. Thus, the provision of effective and tailored care for children and their families has become vital. The social consequences of the COVID-19 pandemic are known everywhere, and among these, it has been argued that the COVID-19 pandemic has had a major impact on PO. Overall, the growth of PO over the last decade has been enhanced by the pandemic. During the COVID-19 pandemic, children, adolescents and young adults gained weight as the pediatric population dealt with sedentary lifestyles and changes in food habits. In this review, we want to highlight the impact that the COVID-19 pandemic had on PO.